Correlation between femoral offset and other morphometric parameters - Jaiswal Pratima; Verma Lakshmi; Ghulyani Tuhin (Wolters Kluwer Medknow Publications, 2017)
Background and aims: Surgeries involving the femur are quite common. The clinical importance of femur in sports biomechanics and rehabilitation is well known. Therefore, its morphometries has orthopedic implications. The present study aims at establishing interrelationship among various external parameters in adult dried femora including femoral offset (FO), neck shaft angle [NSA], femoral anteversion angle [FNA], Neck width [NW], Anterior Neck length [ANL], Posterior Neck length [PNL], Oblique length [OL] and trochanteric oblique length [TOL], Materials and Methods: A total of 100 [50 right and 50 left] intact, dried adult human femora from department of Anatomy, Government Medical College, Kota were included in this study. The FO, NSA and FNA were measured by digital image analysis in 'IMAGEJ' software. OL and TOL were measured using osteometric board. ANL, PNL and NW were recorded using sliding caliper. Statistical analysis was done using SPSS and Microsoft Excel software. The mean values were calculated, relationship between parameters was measured by Pearson's correlation coefficient V. Multiple regression equations were derived in order to calculate FO by other variables. Results: FO showed strong negative correlation with NSA; strong positive correlation with ANL, PNL, NW; moderate positive correlation with OL, TOL; but no relationship with FNA. NSA had moderate negative correlation with NW and weak negative correlation with PNL. NW & ANL had positive correlation with OL, TOL. Conclusion: In our method we used dried, intact bone and digital photographs with standardised method. Therefore it should provide accurate results; in addition it is cost effective. However studies on larger scale are warranted to design implants for Indian population.